Construction of a Banach algebra in summable infinite matrices and its realization of the Gelfand transformation - Lindiarni, Janny; Setya Budhi, Wono (KOMUNITAS Analisis Matematika INDONESIA, 2023)
In this paper, we extend the construction of a Banach Algebra from summable sequences to summable matrices. We also find the representation of the Banach algebra as complex-valued continuous functions defined on a Hausdorff space.